The Role of Biodegradable Polypropylene Mulch on the Growth of Red Chili (Capsicum annuum L.) - Ferdianto Budi Samudra (Politeknik Pembangunan Pertanian Malang, 2022)
The role of mulch in maintaining soil temperature and preventing competition from weeds has been felt by farmers, but the use of mulch is still limited to polyethylene (PE) mulch which is less environmentally friendly. The purpose of this study was to analyze the role of various types of mulch on the Hot Chili varieties of red chili. The method used was a Randomized Block Design (RAK) with 5 (five) treatments and 3 (three) replications. The mulch used consisted of straw mulch, black silver polyethylene (PE) mulch, thin black polyporpylene (PP) mulch, thick black polyporpylene (PP) mulch, gray polyporpylene (PP) mulch, black silver polyporpylene (PP) mulch. The results showed that silver black PP mulch had the same effect as silver black PE and the effect was greater than thin black PP, thick black PP, straw and gray PP on growth observations and total fresh weight of fruit per plant.